Виявлення прихованої пропаганди в медіатекстах - Самелюк, А. А. (ХНУРЕ, 2023)
The rapid development of technology and the ubiquity of the media have led to the spread of media texts containing covert propaganda. Such propaganda aims to influence public opinion, often implicitly, and has serious implications for democratic societies. Methods for detecting and analyzing hidden propaganda in media texts using natural language processing (NLP) methods are researched. Various unsupervised and supervised learning strategies are emphasized, such as topic modeling, clustering, and deep learning methodologies. The significance of devising methods capable of identifying propaganda across diverse languages and cultural settings is addressed. Also, the limitations of these methods are considered